2020
DOI: 10.31459/turkjkin.682436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sixteen week of resistance exercises on some selected cognitive variables development in adolescents with intellectual disabilities

Abstract: Intellectual disabilities a serious problem in the entire world and its prevalence is high in school-age children. These difficulties can influence cognitive, social and emotional areas of functioning and has led their families to suffer in economic and social disadvantages than those without disabilities. The main objective of this study was to investigate the effect of sixteen week resistance exercise on cognition developments of school children with intellectual disabilities in Desse & Kombolcha, Amhara reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The effects of the interventions in the various studies appear similar to those that have been reported following resistance training in the average healthy and intellectually disabled population [ 3 , 22 , 25 , 30 , 33 ]. However, some variability has also been reported in other resistance training studies and those examining other exercise modalities [ 20 , 29 , 46 , 47 , 57 ]. Inherent within any measurement are both technical error and random within-subject variation [ 63 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The effects of the interventions in the various studies appear similar to those that have been reported following resistance training in the average healthy and intellectually disabled population [ 3 , 22 , 25 , 30 , 33 ]. However, some variability has also been reported in other resistance training studies and those examining other exercise modalities [ 20 , 29 , 46 , 47 , 57 ]. Inherent within any measurement are both technical error and random within-subject variation [ 63 ].…”
Section: Discussionmentioning
confidence: 84%
“…These improvements were also associated with improvements in gait speed and balance [ 46 ]. Other non-randomized controlled studies have shown interesting results through the implementation of ST programs in individuals with ID, namely, cognitive effects such as positive changes in working memory, short-term memory, vocabulary knowledge, and reasoning ability [ 57 ], and improved flexibility [ 58 ] and performance in daily life activities [ 59 ]. There is an urgent need for randomized procedures to assess the benefits of these variables and aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation